Bishops and Law Courts in Late Antiquity: How (Not) to Make Sense of the Legal Evidence - Humfress, Caroline (2011)
This article seeks to reevaluate existing scholarship on the late Roman "bishop's hearing" or "bishop's court" via a reexamination of the nature of the extant legal evidence. Paying particular attention to the original contexts in which the relevant fourth- and early fifth-century imperial constitutions were issued, it argues that, prior to the publication of the Theodosian Code in 438, these constitutions should be understood as specific responses to circumstances thrown up by courtroom practice. Having reassessed the nature of the legal evidence both before and after the promulgation of the Theodosian Code, the article attempts to re-contextualize the episcopalis audientia within a broader late Roman socio-legal landscape, hence challenging the traditional framing of the debate on the episcopalis audientia as a question of "church" and "state."